Effect of diet and dietary habits on Jaws of ancient and modern Population in Sudan - Siddiq, Razaz Muhammad; Qaribullah, Abbas (Journal of medical and pharmaceutical sciences, 2024)
Background: The masticatory units are highly affected by diet and dietary habits which are reflected on the jaw size and occlusion. There are morphological differences between the modern population and ancient, like jaws of modern population are smaller, .and project less than those of equivalent sized ancient. Aim: To determine the effect of diet and dietary habits on jaws size (width and length) in both modern and ancient. Method: Across sectional study was done in Khartoum state, comparing ancient from Marawi (albejrawya) and modern population in Khartoum state. 44 samples, 22 jaws of ancient and 22 modern populations participate. The 22 ancient remains were examined and measured directly, while the 22 modern participants filled the diet and dietary questioner then examined orally and the findings recorded on the examination sheet. The jaws measurements for living were done on radiological (OPG&CBCT). Statistical analyses of the data set included univariate analysis to show the relative frequency distribution of each variable on the dental examination sheet. Results: According to the result of overall the median of ancient jaw size maxilla vertical length was 2cm and modern population was1.4cm. The median length of mandible in ancient was 14.1cm and modern population was 13.2cm. The width was 5.2cm in ancient mandible and 4.5cm in modern population mandible. The median width of maxilla ancient was 5.6cm and modern population was 5.3cm.